A Conceptual Framework to Design and Develop Creativity Clay Module to Teach Special Educational Needs (SENs) Students with Learning Disabilities in Primary School - Govindasamy, Parthiban; Abdullah, Noraini Binti; Ibrahim, Rohaizat Binti; May, Yoong Soo (South Asian Journal of Social Sciences and Humanities, 2022)
This paper presents a conceptual framework for design and develop Creativity Clay Module to teach Special Educational Needs (SENs) students with learning disabilities in Special Education Integration Program (SEIP) in Malaysia primary schools. The Creativity Clay Module will be designed especially for students with learning disabilities based on Torrance Creativity Theory, Constructivism Theory, and Sidek’s Module Development Model. Thus, this paper presenting literature review on Creativity, Clay, Torrance Creativity Theory, Constructivism Theory, Sidek’s Module Development Model, Design and Development Research (DDR), Fuzzy Delphi Method (FDM), and SENs Students with Learning Disabilities. Literature review evidenced SENs students with learning disabilities are poor in creative skills. Therefore, there is a need to develop a specific teaching module for SENs students with learning disabilities to cultivate their creativity skills through teaching and learning. Thus, this study aims to present a conceptual framework to design and develop Creativity Clay Module. This study will employ Modified Design and Development Research (DDR) approach. There are three phases in this approach namely; phase one: need analysis; phase two: design and develop; and phase three: evaluation. After gone through the three phases of DDR, researcher will produce the Creativity Clay Module as end product. This Creativity Clay module is able to nurture creativity skills among SENs students with learning disabilities in primary school.
Keywords: Creativity Clay; Special Educational Needs (SENs); Special Education Integration Program (SEIP); Design and Development Research (DDR); Fuzzy Delphi Method (FDM)